Binational cancer patient experiences and cancer coping in a rural US-Mexico border region. Issue 2 (3rd March 2020) - Ko, Eunjeong; Beloshapko, Anastasia V.; Zúñiga, María Luisa; Palomino, Helen; Peacher, Diana; Watson, Mercedes
Abstract: Objective: Coping with cancer is central to patients' cancer recovery and quality of life, yet little is known about cancer experiences and coping from the perspective of binational cancer patients. This brief report provides an exploration of experiences relating to cancer diagnosis/treatment and coping among Latino cancer patients living in the U.S.-Mexico border region Design: We conducted secondary data analysis of qualitative data Participants and methods: We conducted in-depth of interviews with 22 patients from a rural cancer care organization. Thematic analysis was used to analyze the data. Findings: Three themes emerged: 1) changes in sexual functioning, 2) navigating cancer in the U.S. and between Mexican border communities, and 3) social support. Conclusion: Rural Latino cancer patients face multiple challenges in accessing cancer treatments. Social support fills the gaps for their continuum of care. Implication: Promoting culturally-relevant coping and resilience in clinical practice.